Development of Interactive Puzzle Media Based on Critical Reasoning Games for Fine Arts Material for Grade 5 Elementary School - Suryono, Krisna Trijati; Ngazizah, Nur; Suyoto, Suyoto (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to develop and evaluate the feasibility of a game-based interactive puzzle learning media designed to foster critical thinking skills in fifth-grade elementary students. The media are used in the instructional topic “Creating Artworks from Household Waste Materials” to enhance students’ critical reasoning abilities. Methodology: This research employed a Research and Development (R&D) approach based on the ADDIE framework, comprising analysis, design, development, implementation, and evaluation stages. The participants were 20 fifth-grade students. Data were gathered through expert validation forms, teacher and student questionnaires, and pretest–posttest instruments, and then analyzed using Likert-scale scoring and N-Gain testing. Main Findings: The validation results indicated an average score of 4.56 from the material expert, 4.57 from the media expert, and 4.46 from the practitioner, all categorized as highly feasible. Teacher responses reached 97%, while student responses in the limited trial and field trial were 100% and 99%, respectively, indicating a very high level of practicality. The effectiveness of the media was demonstrated by N-Gain scores of 81.90% in the limited trial and 79.28% in the field trial, both of which were classified as high. Novelty/Originality of this study: This study introduces a game-based interactive puzzle media integrated with critical thinking indicators in elementary school visual arts instruction. The media emphasizes not only creativity but also the development of students’ critical thinking skills through contextual problem-solving activities that use household waste materials.